Development of Pesantren Architecture: Literature Review - Shofiyah Nurmasari; Edi Purwanto; Agung Budi Sardjono; Wijayanti Wijayanti (Eduvest - Journal of Universal Studies, 2024)
Pesantren is an institution that contributes to the scholarship of Islam as well as religious societies. It will be a place of learning the science of religion, cultivation of faith and fear of God, character and morality so that it will become a leader and a Muslim scientist that will benefit the society in the future. Islamic education has grown and undergone an exciting shift from the 17th to the 21st century. This shift is part of Kyai's innovative teaching approach that is central to the training, the student's qualitative understanding, not just the cognitive aspects taught in the classroom, and the priority given to the ethical and spiritual aspects of the training. The trainer has to adapt according to the needs and challenges of the moment and of course the presence of the Kyai figure is important in this training. One of today's national challenges is that training plays an important role in promoting moderate Islamic values that tolerate and accept differences. The growth of practitioners as Islamic institutions becomes an opportunity to spread the understanding of moderate Islam, a sustainable life that protects us from chaos. Such development is part of an adaptation to the evolution of the times and to preserve its existence and contribution to the scholarship of Islam. With regard to the diversity of such development, there is a need for a literature review to map the development of the architecture of the country as a fragment of the existing literature.